A Case of Bilateral Uveitis and Papillitis in a Patient Treated with Pembrolizumab. Issue 3 (May 2016) - Abu Samra, Khawla; Valdes-Navarro, Manuel; Lee, Stacey; Swan, Robert; Foster, C. Stephen; Anesi, Stephen D.
Purpose: Drug-induced uveitis is a well-known effect of ocular inflammation that has been reported with many medications. Pembrolizumab is a newer generation of the anti-programmed cell death-1 monoclonal antibodies that was recently approved by the Food and Drug Administration for the treatment of advanced melanoma. Immune-mediated adverse events involving different organs have been reported in recent literature in association with this drug. We present the first reported case of uveitis in association with pembrolizumab therapy. Case report: An 82-year-old man with stage IV melanoma was started on pembrolizumab infusion treatment every 3 weeks. Two months after initiating therapy, he presented with bilateral severe anterior uveitis and papillitis with fast and complete recovery after withholding further pembrolizumab infusions and treatment with topical steroid. Uveitis recurred after restarting pembrolizumab therapy. Conclusions: In current clinical practice, many new drugs are being approved, requiring better characterization of the prevalence, onset, and nature of adverse events in order to aid development of effective management strategies. Ophthalmologists should keep in mind that drugs are always a possible cause of ocular inflammation in patients presenting with uveitis.